Medication for opioid use disorder service delivery in carceral facilities: update and summary report - Justin Berk; Anna-Maria South; Megan Martin; Michael-Evans James; Cameron Miller; Lawrence Haber; Josiah Rich (Health & Justice)
Abstract The opioid overdose crisis intersects critically with the criminal legal system where individuals with opioid use disorder (are significantly overrepresented. Subsequently, incarceration increases the risk of opioid overdose due to reduced tolerance, interrupted social supports, and limited access to treatment. Medications for opioid use disorder (MOUD), such as methadone, buprenorphine, and naltrexone, have been shown to reduce opioid-related mortality and improve outcomes for those in carceral settings. Despite this, access to MOUD in jails and prisons remains limited due to stigma, concerns about medication diversion, and logistical challenges. This paper reviews the current state of knowledge on MOUD in carceral settings, summarizing the prevalence of treatment programs, the role of novel formulations like injectable buprenorphine, and barriers to implementation. It also explores the continuum of care, emphasizing the importance of initiating MOUD during incarceration and ensuring continuation upon release to prevent treatment gaps. Recent policy changes, such as Sect. 1115 Medicaid waivers, offer promising avenues for expanding access, but retention in treatment and post-release outcomes remain significant challenges. The paper provides a comprehensive overview of existing literature and updates on MOUD service delivery, including the impact of recent policy shifts and research on outcomes such as recidivism and health improvement. It concludes by identifying key areas for future research, including strategies to improve treatment retention, address systemic barriers through criminal justice reform, and enhance care coordination during the transition from incarceration to the community.